Addressing the sins of consumer psychology via the evolutionary lens. Issue 2 (7th January 2021) - Saad, Gad
Abstract: As is true of any scientific discipline, consumer psychology faces some challenges, many of which can be ameliorated via the use of evolutionary psychology. This includes broadening the scope of the research questions tackled as well as their interestingness; increasing the epistemological and theoretical scope of the discipline; reducing the likelihood of succumbing to the WEIRD sampling bias; decreasing methodological fixation; increasing interdisciplinarity; and augmenting the ethos of replications as well as the field's consilience via the building of consilient nomological networks of cumulative evidence. Modern‐day consumers exhibit preferences and behaviors that are vestiges of evolutionary forces that occurred long ago in deep evolutionary time. Marketing academics and practitioners alike, seeking to unlock the mysteries of what makes consumers tick, can only be enriched in recognizing that Homo consumericus is a product of the same evolutionary processes that have shaped all life forms. To deny this reality ensures that marketing knowledge will remain largely decoupled from biology, and in doing so engender at best an incomplete understanding of consumer behavior.